PENGARUH PENGGUNAAN MEDIA FILM KARTUN ISLAMI TERHADAP PERILAKU MORAL ANAK USIA 4-5 TAHUN DI TK AL MASRURIYAH KECAMATAN TAMPAN KOTA PEKANBARU - Ernawati Ernawati; Zulkifli Zulkifli; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study are as follows: 1) To determine the moral behavior of children aged 4-5 years prior to the use of media in the Islamic cartoon kindergarten Handsome Al Masruriyah District of the city of Pekanbaru. 2) To know the moral behavior of children aged 4-5 years after the use of cartoons of Islamic kindergarten Handsome Al Masruriyah District of the city of Pekanbaru. 3) To determine the influence of media use cartoon Islamic for Moral Behavior of 4-5 year old children in kindergarten Al Masruriyah Handsome District of the city of Pekanbaru. The research sample is graders B2 consisting of 15 children, consisted of 7 men and 8 women. The sampling technique used is sampling saturated. Collecting data using observation and documentation. The data analysis technique used in this study is t test analysis techniques. From the results obtained with t = 24.67 means greater than ttable the significant level of 5% and at significant level of 1% (2:14 <24.67> 2.98). Thus, it means Ho is rejected. This means There is a significant relationship between the use of media-Islamic cartoons on the moral behavior of children aged 4-5 years in kindergarten Al Masruriyah Handsome District of the city of Pekanbaru. From this study it can be concluded that the effect of media usage Islamic cartoons against moral behavior of children aged 4-5 years in kindergarten Al Masruriyah District of Handsome Pekanbaru, before carrying out experiments beforehand in the form of charging sheet Pre test observations of the child's moral behavior. Pre test results obtained from a total value of 167 and a value of 46.39%. After carrying out the experiment with the use of cartoons of Islamic media application, the next step to implement Post test in the form of sheet charging observation of moral behavior of children. Post test results obtained from a total value of 284 and an average of 78.89%.Keywords: Use of Media Film Cartoon Islami Against Moral Behavior2